2013
DOI: 10.1155/2013/787916
|View full text |Cite
|
Sign up to set email alerts
|

Achyrocline satureioides(Lam.) D.C. Hydroalcoholic Extract Inhibits Neutrophil Functions Related to Innate Host Defense

Abstract: Achyrocline satureioides (Lam.) D.C. is a herb native to South America, and its inflorescences are popularly employed to treat inflammatory diseases. Here, the effects of the in vivo actions of the hydroalcoholic extract obtained from inflorescences of A. satureioides on neutrophil trafficking into inflamed tissue were investigated. Male Wistar rats were orally treated with A. satureioides extract, and inflammation was induced one hour later by lipopolysaccharide injection into the subcutaneous tissue. The num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
16
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 46 publications
5
16
0
6
Order By: Relevance
“…kidney without cellular alterations (Baldissera et al, 2014c). In animals treated with hydroalcoholic extract, A. satureioides did not change the levels of creatinine and urea (Barioni et al, 2013). According to Javaid et al (2012), the A. satureioides is considered in literature as a potent nephroprotective plant.…”
Section: Discussionmentioning
confidence: 99%
“…kidney without cellular alterations (Baldissera et al, 2014c). In animals treated with hydroalcoholic extract, A. satureioides did not change the levels of creatinine and urea (Barioni et al, 2013). According to Javaid et al (2012), the A. satureioides is considered in literature as a potent nephroprotective plant.…”
Section: Discussionmentioning
confidence: 99%
“…More particularly, there are several reports indicating that tea prepared mainly by communities of South Brazil, from the inflorescences of A. satureioides , leads to the relief of the symptoms of gastric ulcers [10, 11] and inflammatory diseases of the gastrointestinal tract, such as Crohn's disease [11, 12]. In line with its traditional use, the anti-inflammatory activity of extracts from A. satureioides has been confirmed in different studies [11, 13, 14]. Santin et al [15] previously confirmed the antiulcer gastric potential of this plant and its antispasmodic effect in gastrointestinal smooth muscle preparation has also been described [13].…”
Section: Introductionmentioning
confidence: 90%
“…However, despite these findings and popular usage to treat IBD, no reports are available about the intestinal anti-inflammatory effects A. satureioides preparations. Therefore, the present study has been designed to examine the intestinal anti-inflammatory effects of the hydroalcoholic extract of inflorescences of A. satureioides (HEAS), which has already been chemically characterized being the major components identified as quercetin and luteolin [14], in dextran sulfate sodium (DSS) induced colitis in mice.…”
Section: Introductionmentioning
confidence: 99%
“…[21,48] It is a plant that works to reduce the influx of neutrophils and secretion of leukotriene B4 at the site of inflammation, blocking the expression/activity of molecules involved in the interaction between immunocirculating cells and endothelial cells, reducing the body's innate response without causing systemic toxicity. [49] Aqueous and ethanolic extracts of A. satureioides promote proliferation of keratinocyte and human lung fibroblasts lines cells mainly at low concentrations without showing cytotoxicity at higher concentrations in vitro [50] reinforcing its popular use for wound healing by acting in different stages of the repair process of injured tissues and in intensified inflammatory processes, this bio-activity is an important therapeutic strategy.…”
Section: Who Traditional Medicinementioning
confidence: 99%